Photosynthesis and chlorophyll fluorescence of Iranian licorice (Glycyrrhiza glabra l.) accessions under salinity stress - Mousavi, Seyyed Sasan; Karami, Akbar; Maggi, Filippo (Frontiers in Plant Science, 2022)
While salinity is increasingly becoming a prominent concern in arable farms around the globe, various treatments can be used for the mitigation of salt stress. Here, the effective presence of Azotobacter sp. inoculation (A1) and absence of inoculation (A0) was evaluated on Iranian licorice plants under NaCl stress (0 and 200 mM) (S0 and S1, respectively). In this regard, 16 Iranian licorice (Glycyrrhiza glabra L.) accessions were evaluated for the effects on photosynthesis and chlorophyll fluorescence. Leaf samples were measured for photosynthetic pigments (via a spectrophotometer), stomatal and trichome-related features (via SEM), along with several other morphological and biochemical features. The results revealed an increase in the amount of carotenoids that was caused by bacterial inoculation, which was 28.3% higher than the non-inoculated treatment. Maximum initial fluorescence intensity (F0) (86.7) was observed in the ‘Bardsir’ accession. Meanwhile, the highest variable fluorescence (Fv), maximal fluorescence intensity (Fm), and maximum quantum yield (Fv/Fm) (0.3, 0.4, and 0.8, respectively) were observed in the ‘Eghlid’ accession. Regarding anatomical observations of the leaf structure, salinity reduced stomatal density but increased trichome density. Under the effect of bacterial inoculation, salinity stress was mitigated. With the effect of bacterial inoculation under salinity stress, stomatal length and width increased, compared to the condition of no bacterial inoculation. Minimum malondialdehyde content was observed in ‘Mahabad’ accession (17.8 μmol/g FW). Principle component analysis (PCA) showed that ‘Kashmar’, ‘Sepidan’, ‘Bajgah’, ‘Kermanshah’, and ‘Taft’ accessions were categorized in the same group while being characterized by better performance in the aerial parts of plants. Taken together, the present results generally indicated that selecting the best genotypes, along with exogenous applications of Azotobacter, can improve the outcomes of licorice cultivation for industrial purposes under harsh environments.